Menyingkap Akar Ideologi Lirik Lagu “Epiphany”: Analisis Tiga Kode Narasi Roland Barthes - Koesworo Setiawan (Ranah: Jurnal Kajian Bahasa, 2026)
This article aims to construct the core meaning, identify the ideological roots, and explain how the ideology of the song "Epiphany" sung by Kim Seok-jin (a member of the vocal group BTS) was formed. Data validity was achieved through data triangulation, namely by combining primary data in the form of the lyrics of the song "Ephipany" with secondary data from relevant literature. Data was observed by examining all the song lyrics and cross-analyzing them. The lyrics were categorized into three narrative codes according to Roland Barthes: semantic, symbolic, and cultural. The lyrics were interpreted through Barthes's three main concepts: denotation, connotation, and myth. This study found that three codes appeared simultaneously relatively consistently in almost every verse. The symbolic code constructs the strong hegemony of idolatry. The semantic code conveys the severity of inner turmoil in the fight against hegemony. The cultural code describes the changes in attitudes and perspectives that pose a challenge to the destruction of hegemony. In conclusion, the core meaning of the song lyrics is success in being yourself (“self-love”). Self-love is an ideology formed through three transitional phases: the hegemony of idol figures, breaking free from idolatry (self-reflection), and believing in one's own abilities. Abstrak Artikel ini bertujuan untuk mengkonstruksi makna inti, mengidentifikasi akar ideologis, dan bagaimana proses terbentuknya ideologi dari lagu “Epiphany” yang dinyanyikan oleh Kim Seok-jin (personel grup vokal BTS). Validitas data ditempuh dengan teknik triangulasi data, yakni dengan memadukan data primer berupa lirik lagu “Ephipany” dengan data sekunder yang diperolah dari literatur yang relevan. Data diobservasi dengan memeriksa seluruh lirik lagu dan menganalisis secara silang. Lirik dikategorisasi dengan tiga kode narasi Roland Barthes: semantik, simbolik dan budaya. Lirik dimaknai berdasarkan tiga konsep utama Barthes: denotatif, konotatif dan mitos. Penelitian ini menemukan tiga kode muncul secara bersamaan relatif konsisten pada hampir setiap bait. Kode simbolik mengkonstruksi kuatnya hegemoni pengaruh dari idola. Kode semantik menunjukkan kerasnya pergolakan batin selama melawan hegemoni. Kode budaya menggambarkan perubahan sikap dan cara pandang yang berjalan penuh tantangan untuk meruntuhkan hegemoni. Kesimpulannya, makna inti lirik lagu adalah sukses menjadi diri sendiri (self love). Self love merupakan ideologi yang terbentuk dari tiga fase transisi: hegemoni sosok idola, keluar dari pengaruh idola (refleksi diri), dan percaya kemampuan diri sendiri.